Iraq : First Review Under the Stand-By Arrangement and Financing Assurances Review Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The First Review under the Stand-By Arrangement (SBA) discusses policies focused on measures to accelerate the reconstruction of the Iraqi economy while maintaining macroeconomic stability. Inflation has slowed down, and monetary and exchange rate policies have been adjusted. The Central Bank of Iraq (CBI) will increase the pace of appreciation of the dinar and keep the policy interest rate positive in real terms to keep inflation under control. Restructuring plans for the two largest state-owned banks will be developed on the basis of their finalized financial and operational audits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet